Looking to the Future of Bali Tourism: Strategy for Sustainable Governance Transformation in Law No. 15 of 2023 - A.A Bagus Adhi Mahendra Putra; I Made Subawa; Putu Gede Arya Sumerta Yasa; Desak Putu Dewi Kasih (Journal of Legal and Cultural Analytics, 2025)
Bali's tourism plays a crucial role in Indonesia's economy but has negative environmental and socio-cultural impacts due to rapid growth. Law No. 15 of 2023 marks a significant step toward sustainable tourism governance by regulating natural, cultural, and social resource management. This study uses a qualitative descriptive approach, with literature reviews and interviews with policymakers, industry players, and local communities, to explore the strategy for transforming Bali's tourism governance under this law. Results show that the law strengthens community participation and conservation, yet challenges remain in implementation and the need for better collaboration among stakeholders. The study highlights the importance of consistent regulation and collaboration in achieving sustainable tourism in Bali.